Guiding Principles for the Clinical Use and Selection of Microcatheters in Complex Coronary Interventions - Goel, Pravin K.; Sahu, Ankit Kumar; Kasturi, Sridhar; Roy, Sanjeeb; Shah, Nimit; Parikh, Prakashvir; Chadha, Davinder S. (Frontiers in Cardiovascular Medicine, 2022)
Therapeutic approach, using microcatheters as a coronary interventional tool is growing among cardiologists across the country, for complex coronary interventions like bifurcation lesions, ostial location, tortuous anatomy, angled takeoffs, coronary calcification, and chronic total occlusion PCI. During treatment of such complex lesions, microcatheters are an essential part of the tool kit with both single lumen and dual lumen microcatheters having their specific niche areas. Microcatheter selection includes a detailed understanding of the microcatheter specification, lesion anatomy, lesion location, vessel tortuosity and trajectory, and crossing techniques. Selecting appropriate crossing techniques with different microcatheters increases success rates of percutaneous coronary intervention (PCI), reduces procedure time, lowers radiation, and contrast use. However, microcatheter utility and the technicalities of their use is not yet fully realized by many operators and their true scope has not been fully explored. This article discusses and summarizes the thoughts and key opinions of leaders in this field.